2003
DOI: 10.1038/sj.bjc.6600708
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferase M1 and T1 genetic polymorphisms, alcohol consumption and breast cancer risk

Abstract: Alcohol consumption has been inconsistently associated with breast cancer risk. Recent studies suggest that genetic polymorphisms of glutathione S-transferases (GSTs) may modify this relation. To determine if breast cancer risk is associated with GSTM1 and GSTT1 genetic polymorphisms, and to evaluate the effect modification between GST genotypes and alcohol consumption in the risk of breast cancer, we conducted a case -control study in the state of Connecticut in the period 1998 and 2001. Cases were histologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 21 publications
4
42
1
3
Order By: Relevance
“…10-5.90). An effect of GSTT1 null genotype on breast cancer risk is in agreement with three previous studies [24][25][26] but such risk was not observed in eight other studies [27][28][29][30][31][32][33][34]. Our observation may be a chance finding, also in view of the absence of an association for current smokers, even for those who smoke more than 20 cigarettes per day.…”
Section: Discussionsupporting
confidence: 92%
“…10-5.90). An effect of GSTT1 null genotype on breast cancer risk is in agreement with three previous studies [24][25][26] but such risk was not observed in eight other studies [27][28][29][30][31][32][33][34]. Our observation may be a chance finding, also in view of the absence of an association for current smokers, even for those who smoke more than 20 cigarettes per day.…”
Section: Discussionsupporting
confidence: 92%
“…Out of the 161 abstracts retrieved through the search criteria, 94 were irrelevant, nine articles [35][36][37][38][39][40][41][42][43] were excluded because they were conducted on overlapping populations with other eligible studies [6,8,20,25,30,44,45] (these excluded articles represent smaller studies performed on subsets of larger eligible studies), five studies [46][47][48][49][50] were excluded given that they have not included controls in their study design, two articles [4,51] were reviews/meta-analyses, and three studies [52][53][54] were excluded due to other reasons (two of them [52,53] was excluded due to reporting reasons, i.e. no reporting of the relevant genotype frequencies, whereas the other [54] was excluded for examining the association between GSTA1 polymorphism and survival after breast cancer treatment At the overall analysis, the null GSTT1 genotype was associated with elevated breast cancer risk (pooled OR=1.114, 95%CI: 1.035-1.199, random effects).…”
Section: Resultsmentioning
confidence: 99%
“…In the present meta-analysis, such subanalyses have not been presented after carefully taking into account that solely ten [6,9,15,28,44,58,65,67,69,70] out of 41 studies on GSTT1 and nine [15, 28-32, 65, 67, 70] out of 30 studies on GSTP1 status have presented subanalyses on pre-and postmenopausal women. Indeed, the power of the above subsets of studies was so limited that the main associations were blurred (data not shown); as a result, proceeding to subanalyses on pre-and postmenopausal subjects did not seem of particular value.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of individuals who do not express the enzyme is higher in Asians (60%) and Africans (40%) than in Caucasoids (20%). 21,22 The polymorphisms of the GSTM1 and GSTT1 genes involved may result in differences in the enzymatic activity, possibly favoring mechanisms that increase the susceptibility to cancer. Studies relating these polymorphisms of deletion with the occurrence of head and neck carcinoma diverge between themselves: some demonstrate the association of these neoplasias with the null genotype of GSTM1, 7,21,[23][24][25] while others do not.…”
Section: Original Article Introductionmentioning
confidence: 99%
“…21,22 The polymorphisms of the GSTM1 and GSTT1 genes involved may result in differences in the enzymatic activity, possibly favoring mechanisms that increase the susceptibility to cancer. Studies relating these polymorphisms of deletion with the occurrence of head and neck carcinoma diverge between themselves: some demonstrate the association of these neoplasias with the null genotype of GSTM1, 7,21,[23][24][25] while others do not. [26][27][28][29][30] The same occurs with the null genotype of GSTT1, showing an association with the disease 7,23,25 or not.…”
Section: Original Article Introductionmentioning
confidence: 99%